Achieving International Society for Pediatric and Adolescent Diabetes and American Diabetes Association clinical guidelines offers cardiorenal protection for youth with type 1 diabetes. Issue 1 (February 2015) - Bjornstad, Petter; Pyle, Laura; Nguyen, Nhung; Snell‐Bergeon, Janet K; Bishop, Franziska K; Wadwa, R Paul; Maahs, David M
<x xml:space="preserve">Abstract</x> Objective Most youth with type 1 diabetes do not meet the American Diabetes Association (ADA) and International Society for Pediatric and Adolescent Diabetes (ISPAD) targets for hemoglobin A1c (HbA1c), blood pressure (BP), lipids, and body mass index (BMI). We hypothesized that ISPAD/ADA goal achievement at baseline would be associated with cardiorenal risk factors at baseline and 2 yr follow‐up in adolescents with type 1 diabetes. Methods We assessed the cross‐sectional and longitudinal relationships between ISPAD/ADA goal achievement at baseline and cardiorenal health at baseline and 2‐yr follow‐up (n = 297; 15.4 ± 2.1 yr at baseline) in adolescents with type 1 diabetes. Goal achievement was defined as HbA1c < 7.5%, BP < 90th percentile for age, sex, and height, low density lipoprotein‐cholesterol (LDL‐C) <100 mg/dL, high density lipoprotein‐cholesterol (HDL‐C) >35 mg/dL, triglycerides (TG) <150 mg/dL and BMI <85th percentile for age and sex. Cardiorenal outcomes included pulse‐wave velocity (PWV), brachial distensibility (BrachD), augmentation index (AIx), and epidermal growth factor receptor (eGFR) continuously and categorically as hyperfiltration (eGFR ≥ 135 mL/min/1.73 m2). Results Adolescents with type 1 diabetes who met 1–3 goals, had significantly greater (P < 0.05) baseline PWV (5.1 ± 0.1 vs. 5.4 ± 0.1 m/s), follow‐up PWV (5.5 ± 0.1 vs. 5.7 ± 0.1 m/s), greater follow‐up eGFR (104 ± 2 vs. 116 ± 3 mL/min/1.73 m2), and greater odds of renal hyperfiltration at follow‐up (odds ratio (OR): 20.0, 95% confidence interval (CI): 3.8–105.2) compared to those who met 4–6 goals after adjusting for Tanner stage, sex, age, and diabetes duration. No statistically significant differences in the cardiorenal outcomes were observed between adolescents with type 1 diabetes who met 4–6 goals and non‐diabetic controls (n = 96). Conclusions In adolescents with type 1 diabetes, baseline ADA/ISPAD goal achievement was associated with cardiorenal protection at baseline and 2‐yr follow‐up.